2005
DOI: 10.1093/rheumatology/keh535
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of intra-articular triamcinolone and/or physiotherapy in shoulder capsulitis

Abstract: Corticosteroid injection is effective in improving shoulder-related disability, and physiotherapy is effective in improving the range of movement in external rotation 6 weeks after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
159
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(168 citation statements)
references
References 29 publications
1
159
2
6
Order By: Relevance
“…Although this study was well controlled, the placebo group (intra-articular saline injection and a HEP) is considered by others to be an effective treatment for adhesive capsulitis. 19,61 Ryans et al 117 also investigated the effect of steroid injections and physiotherapy, performing both glenohumeral joint intra-articular and subacromial injections. Patients were classified as having adhesive capsulitis and included in this study if they had a painful shoulder in the fifth cervical nerve root dermatome distribution of more than 4 weeks and less than 6 months in duration, and a limitation of active and passive range of movement greater than 25% in abduction and external rotation compared to the uninvolved, contralateral shoulder.…”
Section: Corticosteroid Injectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study was well controlled, the placebo group (intra-articular saline injection and a HEP) is considered by others to be an effective treatment for adhesive capsulitis. 19,61 Ryans et al 117 also investigated the effect of steroid injections and physiotherapy, performing both glenohumeral joint intra-articular and subacromial injections. Patients were classified as having adhesive capsulitis and included in this study if they had a painful shoulder in the fifth cervical nerve root dermatome distribution of more than 4 weeks and less than 6 months in duration, and a limitation of active and passive range of movement greater than 25% in abduction and external rotation compared to the uninvolved, contralateral shoulder.…”
Section: Corticosteroid Injectionsmentioning
confidence: 99%
“…Results are inconsistent across multiple studies, demonstrating that stretching results in minimal or no difference in outcomes (at 3-6 months) in patients treated with a therapistdirected HEP or other interventions. 19,23,61,117 There is only 1 study 45 for which the authors fully described the exercises performed, with the other studies simply describing the program as active and/or passive exercises. No evidence exists to guide the optimal frequency, number of repetitions, or duration of stretching exercises.…”
Section: Stretching Exercisesmentioning
confidence: 99%
“…The median time to recovery was 10-12 months and operative cases were 4.8 to 8.8 % in this study, which were superior or equivalent to the previous reports. The type of corticosteroid, the dosage, and frequency of the injection vary from study to study [10,12,14]. The injections of 4-mg dexamethasone were conducted once a week in this study until pain was relieved, which had the effect of reducing synovial inflammation and subsequent capsular fibrosis and allowed improvement of motion with a decreased time to functional recovery [24].…”
Section: Discussionmentioning
confidence: 99%
“…Shaffer et al reported persistence of symptoms and impaired range of motion especially in external rotation in over 50 % of cases at a seven-year follow-up [3]. Conservative treatment for stiff shoulder includes oral administration of non-steroidal anti-inflammatory drugs, oral administration or intra-articular injection of corticosteroid, and physiotherapy [2,[10][11][12][13][14][15]. During these treatment modalities, the efficacy of intra-articular injection of corticosteroid for patients in the freezing phase and that of physiotherapy for patients in the frozen phase are well described [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation